Advancing the science of coordinations - the dynamics of coordinations - Kelso, M. S. (First international symposium sciences and practices in swimming, 2006)
I was very pleased to accept the organizer's invitation to participate in this colloquium. I work at the University of Florida Atlantic on the Atlantic coast. I thought about two titles for today's lecture. The first was "Advancing the science of coordinations" and the second was "Complementary nature". Both of these titles would be appropriate because they call upon two themes which, for me, cannot be dissociated. The first theme concerns dynamic Schemas, self-organization of behaviours, and the brain. Dynamic Schemas describe the way coordination occurs, the way they are formed, adapt, and modify within a natural System such as the human being. There are different types of Systems and different levels of description. For example, one can distinguish a global level, walking or running for instance, and a cerebral level for everything that is going on inside my brain when I walk and when I speak. The science of coordination approaches the subject of coordination within certain parts of the human System, but also within different Systems of different nature, for example of coordination between a group of individuals. The second theme of complementary nature is concerned directly with the human tendency to separate the world into dichotomous categories (body-mind, nature-culture, good-evil). One of the complementarities which is our target is the complementarity between philosophy and science which seems to have lost the art of communication. It seems to me high time to reconcile our love of wisdom with our need for knowledge.